Use of TRIZ principles in car design - Lai, Chee Cieh (2012)
Urban congestion and fast-paced society increase the awareness of save space and time in car design. TRZ, a resolution of problems technical and physical contradictions that creates ideal systems and solutions, was studied for its application in car design to achieve space and time saving. In this report, history of automotive industry was briefly narrated to give a basic understanding of development of some car elements and design trends. 40 TRIZ Inventive Principles were applied in generating design solutions intended to eliminate excessive space and time consumption. To investigate the popularity of suggested solutions, questionnaires were designed and conducted with respondents who had sufficient driving experience. Feasibility of suggested solutions then was further discussed with their contradictions, manufacturability and cost-effectiveness.